Disclosure of suicidal thoughts and behaviors: The impact of suicide event type. Issue 12 (25th April 2022) - Ammerman, Brooke A.; Park, Yeonsoo; O'Loughlin, Caitlin M.
Abstract: Objectives: Despite its importance, limited work has investigated the nuances of suicidal thoughts and behavior self‐disclosure. The present study aimed to examine potential differences in self‐disclosure based on whether an individual has disclosed suicidal thinking versus behavior. Methods: Two hundred and four participants having disclosed their suicidal thoughts or behaviors completed a battery of online questionnaires assessing several key aspects of disclosure (i.e., disclosure recipient, perceived helpfulness of disclosure, impact on treatment seeking), as it pertained to both one's first and overall disclosure experiences. Results: Individuals who disclosed a suicide attempt, versus ideation, were more likely to have disclosed to a formal support (i.e., health professional) and to seek professional help following disclosure. No significant group differences in perceived helpfulness of experiences were found. Conclusion: It may be beneficial to increase opportunities for disclosure of suicidal thinking. Overall, disclosures were perceived as helpful and may not impede future help‐seeking behavior.